Analytical Solutions for Gas-Water Two-Phase Flow in Multiseam Coalbed Methane Production - Xiaoji Shang; Zhizhen Zhang; Yixin Niu; Xiao Yang; Feng Gao (Geofluids)
Multiseam coalbed methane (CBM) exploitation can not only reduce single-well investment but also increase the length of service of the well and significantly enhance the CBM economic recovery of the entire basin. To compare with and further to guide the actual project of CBM production, this study proposed a conceptual gas-water two-phase separate flow model for single coal seam considering the solubility of gas. This mathematical model was solved analytically by separation of variables and verified through history matching of the production data from the No. 3 seam of 1# test well of Jincheng and then applied to investigate the effect of gas solubility on the gas pressure. Furthermore, based on the coupled two-phase separate flow model of single seam, another two-phase separate flow model for the development of multicoal seam development was established. Similarly, the analytical solution of this model for multicoal seam layers was matched with the in situ data of TS-1 well of Liupanshui coal mine. It is found that the height difference and pressure difference between the two seams play key roles in the multiseam CBM development comprehensively.